An Algorithm for Reducing the Matrix Norm (Journal of Computational Mathematics, 2018)
Based on the singular decomposition of $2×2$ matrix an algorithm for reducing the matrix norm is presented. Under the optimal choice of the parameters the matrix B after transformation may be considered as "Locally normal", that is, the four corresponding elements of $BB^T-B^TB$ are zero.